Brain “fog,” inflammation and obesity: key aspects of neuropsychiatric disorders improved by luteolin - Theoharides, Theoharis C.; Stewart, Julia M.; Hatziagelaki, Erifili (Frontiers in Neuroscience, 2015)
“Brain fog” is a constellation of symptoms that include reduced cognition, inability to concentrate and multitask, as well as loss of short and long term memory. “Brain fog” characterizes patients with autism spectrum disorders (ASDs), celiac disease, chronic fatigue syndrome, fibromyalgia, mastocytosis and postural tachycardia syndrome (POTS), as well as “minimal cognitive impairment,” an early clinical presentation of Alzheimer’s disease (AD), and other neuropsychiatric disorders. “Brain fog” may be due to inflammatory molecules, including adipocytokines and histamine released from mast cells (MCs) further stimulating microglia activation, and causing focal brain inflammation. Recent reviews have described the potential use of natural flavonoids for the treatment of neuropsychiatric and neurodegenerative diseases. The flavone luteolin has numerous useful actions that include: anti-oxidant, anti-inflammatory, microglia inhibition, neuroprotection, and memory increase. A liposomal luteolin formulation in olive fruit extract improved attention in children with ASDs and "brain fog" in mastocytosis patients. Methylated luteolin analogues with increased activity and better bioavailability could be developed into effective treatments for neuropsychiatric disorders and "brain fog."